2016
DOI: 10.12809/hkmj154604
|View full text |Cite
|
Sign up to set email alerts
|

A case of refractory seizure with cognitive impairment due to anti-GABA encephalitis

Abstract: A 57-year-old man presented with first episode of loss of consciousness at work in February 2014. He experienced no symptoms prior to this syncope event. He was witnessed by his colleagues to have tonic rigidity over his upper limbs, with a bite mark evident over the lateral aspect of his tongue. He had experienced a right-sided temporal headache characterised as dull and persistent for 3 weeks prior to this incident without any precipitating factors or aura identified.He enjoyed good past health and had been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…An interesting commonality between these three cases and our pa-tient's case is that immunotherapy was initiated after nonseizure limbic symptoms emerged. In two patients, followup MRI scans revealed emergent abnormalities (5,6), but the third patient, like ours, exhibited no abnormal findings in follow-up MRI scans (7). As mentioned earlier, some case reports showed abnormalities in PET or SPECT images (7-9), but our patient exhibited no abnormalities in ASL perfusion MRI or perfusion SPECT images.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…An interesting commonality between these three cases and our pa-tient's case is that immunotherapy was initiated after nonseizure limbic symptoms emerged. In two patients, followup MRI scans revealed emergent abnormalities (5,6), but the third patient, like ours, exhibited no abnormal findings in follow-up MRI scans (7). As mentioned earlier, some case reports showed abnormalities in PET or SPECT images (7-9), but our patient exhibited no abnormalities in ASL perfusion MRI or perfusion SPECT images.…”
Section: Discussionsupporting
confidence: 71%
“…Intern Med 59: 843-847, 2020 DOI: 10.2169/internalmedicine.3652-19 In recent case series studies, approximately one third (27-44%) of patients with GABABR-AE had normal brain MRI findings, most of which were probably obtained in the disease's early phase (1-4). Interestingly, a few case studies concerning patients with GABABR-AE reported that normal MRI findings were observed in early-phase GABABR-AE but that MRI abnormalities were observed during symptom progression (5,6). This suggests that the emergence of MRI abnormalities tends to accompany clinical progression in GABABR-AE.…”
Section: Discussionmentioning
confidence: 99%